Insect Collection and Identification : Techniques for the Field and Laboratory. - Gibb, Timothy J.; Oseto, Christian (San Diego : Elsevier Science & Technology, 2019)
Insect Collection and Identification: Techniques for the Field and Laboratory, Second Edition, is the definitive text on all aspects required for collecting and properly preparing specimens for identification. This book provides detailed taxonomic keys to insects and related arthropods, giving recent classification changes to various insect taxa, along with updated preservation materials and techniques for molecular and genomic studies. It includes methods of rearing, storing and shipping specimens, along with a supporting glossary. New sections provide suggestions on how insects and other arthropods can be used within, and outside, the formal classroom and examine currently accepted procedures for collecting insects at crime scenes. This book is a necessary reference for entomology professionals and researchers who seek the most updated taxonomy and techniques for collection and preservation. It will serve as a valuable resource for entomology students and professionals who need illustrative and detailed information for easy arthropod identification.
1.17.2.9 Dimethyl sulfoxide1.17.3 Preservatives in traps; 1.17.3.1 Water and detergent; 1.17.3.2 Ethanol fuel; 1.17.3.3 Sodium dodecyl sulfate and ethylenediaminetetraacetic acid; 1.17.3.4 Propylene glycol; 1.17.3.5 Formaldehyde; 1.17.4 Pinned specimens (Natural History Museum Collections); 1.17.5 Nondestructive methods; 1.17.5.1 Sonication; 1.18 Vouchuring specimens; 2 Agents for killing and preserving; 3 Storage of specimens; 3.1 Temporary storage; 3.1.1 Refrigeration; 3.1.2 Dry preservation; 3.1.3 Papering; 3.2 Mounting specimens; 3.2.1 Preparing dry specimens for mounting
Print version record.
3.2.2 Degreasing
Master record variable field(s) change: 050, 650 - OCLC control number change
Keywords: Insects -- Collection and preservation; Insects -- Identification; Mites -- Collection and preservation; Mites -- Identification; Arthropoda -- Collection and preservation; Arthropoda -- Identification; Arthropoda; Arthropoda -- Collection and preservation; Insects; Insects -- Collection and preservation; Mites; Mites -- Collection and preservation